Development of Mobile Augmented Reality-Based Boarding House Search Application - Pamungkas, Awanda Bintang; Astrianty, Ledy Elsera (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This research focuses on developing a mobile application for boarding house search utilizing Augmented Reality (AR) technology. The application integrates AR features to provide an interactive and immersive experience, enabling users to visualize boarding houses in 3D and explore detailed information in real time. The ADDIE model was adopted as the development framework, encompassing Analysis, Design, Development, Implementation, and Evaluation phases. The application features include a 360-degree view, GPS navigation, real-time updates, and an intuitive user interface to enhance the boarding house search process. Black box testing results indicate that the system performs efficiently across key functionalities such as registration, login, navigation, and booking. The findings demonstrate the potential of AR technology to address challenges in property search, offering innovative solutions for both users and property owners. This study contributes to the advancement of AR-based applications in the housing sector, emphasizing their role in improving user satisfaction and decision-making.